Serum cortisol as a systemic marker in the long-term treatment with fluticasone propionate (FP) in recurrent airways obstruction (RAO) aged horses. - Muñoz Díaz, Trohadio Tomas; Jiménez, Danilo Franco (Revista Científica de la Facultad de Ciencias Veterinarias, 2014)
Â This is the first fluticasone propianato (FP) long-term study in Recurrent Airways Obstruction (RAO)-aged horses (Equus ferus caballus) that compare Fluticasone Propionate (FP) treatment regimens, as well as FP treatment vs. environmental control, over Hypothalamus Pituitary adrenal (HPA) axis, its reversibility and cortisol suppression clinical consequences. The goal was to follow-up RAO clinical signs and cortisol levels in aged RAO-horses treated with FP. Eleven horses were stabled in moldy-dusty conditions to cause RAO disease. Once they were RAO symptomatic, they were divided in two groups: RAO-FP (treatment group) that were kept over hay/straw and RAO-control (non-treatment) that were kept over pellets/wood shavings by six months. After that, all the horses were kept on the paddock and pasture. FP (Flovant HFA®) 2000Âµg B.I.D.(twice-a-day) during six months and 2000Âµg S.I.D. (once-a-day) during other five months was given using Aero- mask®. Clinical respiratory signs (CRS) were also recorded (nasal flaring and abdominal movement). Cortisol was meas- ured using commercial chemiluminescence (CEIA) kit (Immu- lite 1000®, Siemens) -12, -10 d before and 7, 28, 80,160,200,250,290, 320 d after treatment. Cortisol was used as systemic biomarker in determining any potential suppression and general effect related to FP treatment. FP 2000Âµg B.I.D. was associated with a decrease in blood cortisol levels on 28, 80 and 160 d in RAO-horses, however cortisol levels returns similar to baseline values, as well as similar to cortisol values in RAO-control horses when same FP dose was given just S.I.D. These results suggest that long-term 2000Âµg/horse B.I.D. inhaled FP treatment suppresses endogenous cortisol through its action over the hypothalamic”“pituitary”“adrenal (HPA) axis. Cortisol suppression with FP 2000 Âµg/horse B.I.D., may have deleterious effects if suppression is main- tained for more than six months in those aged horses,proving that FP dose should be adjusted and combined with environ- mental management, according to clinical signs improvement.